Global Response towards the Transnationalism of Illegal Rhinoceros Commodity Hunting and Trading in South Africa - Numadi, Katong Ragawi; Ma'rifat, Filasafia Marsya (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2023)
Globalization, which coincides with the formation of a global economic network, has provided convenience in various aspects as well as created new threats, one of them is illegal poaching and illegal trade in wildlife commodities. This is illustrated in this paper through the integration of Africa into the dynamics of the global economy which also has a negative impact in the form of increasing cases of illegal poaching and trade in wildlife commodities, especially African rhino species. The results of this qualitative research found that the issue of poaching wild rhinos in the African region experienced a drastic increase in the early 2010s and reached its peak in 2016 with South Africa as the hotspot as well as the starting point of the supply chain on this issue. Even though the South African government has ratified the Convention on International Trades on Endangered Species of Wild Flora and Fauna (CITES) and made various prevention efforts, the South African government is still experiencing bureaucratic limitations and conflicts of interest in dealing with this issue. As a result, the